The Relationship Between Kinesthetic Learning Style and Academic Anxiety Levels of High School Students - Aslan, Deniz; Ananda, Rizky; Prayoga, Putra (Acta Psychologia, 2025)
This study investigates the relationship between the kinesthetic learning style and academic anxiety levels among high school students. As classrooms continue to favor visual and auditory teaching methods, students with a preference for kinesthetic learning those who learn best through movement and hands-on activities may struggle to adapt, potentially leading to increased academic anxiety. Using a quantitative correlational research design, data were collected from 200 high school students through the VARK Learning Styles Inventory and the Academic Anxiety Scale for Students (AASS). The results revealed a statistically significant positive correlation (r = 0.41, p < 0.01) between kinesthetic learning preference and higher academic anxiety levels. This suggests that students whose learning needs are not adequately addressed in traditional instructional settings are more prone to stress and emotional discomfort in academic situations. The findings highlight the importance of incorporating more inclusive, movement-based learning strategies into classroom instruction. Implications of the study point to the need for adaptive teaching approaches, improved classroom management strategies, and targeted support from school counselors to reduce academic anxiety and promote emotional well-being among kinesthetic learners.